Does it Come in Orange? - Torgeir Norheim (Oz, 1999)
OBJECTIVE READING - WHAT IS THE NATURE OF ARCHITECTURE? Architecture is primarily a synthesis of technology and art. Technology provides the tools and the knowledge to erect pillars, walls, beams, and roofs.